PENGARUH KEPUASAN PETERNAK TERHADAP KINERJA USAHA PETERNAK DALAM POLA KEMITRAAN SISTEM CONTRACT FARMING PETERNAK AYAM BROILER DI KOTA PEKANBARU - fakhri fitriono (Jurnal Agribisnis, 2021)
ABSTRACT This study aim to 1.)determine the level of satisfaction of plasma broiler breeders in partnership 2.)determine the level of peformance of plasma broiler breeders in partnership 3.) analyze the effect of satisfaction to plasma broiler breeders peformance in partnership at Pekanbaru. The partnership that run is contract farming partnership which the company as inti and the breeders as the plasma. This type of research is using the secundary and the primary data, the secundary data is obtained by statistic center, the primary data is obtained by spreading questionaries to 40 respondent which are using non probability sampling technique. Then data analyze both qualitative and quantitative, qualitative data is the interpretation of the likert scale and the interpretation of the quantittative data is linear multiple regression by SPSS for windows 23 include : coefficient of determination, F test, and T test. This research had 7 indicator variables of breeders peformance, the result of likert scale show the value of satisfaction is 3.57, it meants generally plasma breeders be criteria satisfied. The value of peformance is 3.17, it meants that generally peformance of plasma breeders be criteria good enough. The result of multiple regression show that coefficient of determination is 0.727, it meants 72.7 percent satisfaction significant affecting peformance of plasma boriler breeders, while 27.3 percent remains is affect by another variabel beyond the equation model.